Copper tolerance mediated by polyphosphate degradation and low-affinity inorganic phosphate transport system in Escherichia coli - Grillo Puertas, Mariana (2014)
Metal tolerance in bacteria has been related to polyP in a model in which heavy metals stimulate the polymer hydrolysis, forming metal-phosphate complexes that are exported. As previously described in our laboratory, Escherichia coli cells grown in media containing a phosphate concentration >37 mM maintained an unusually high polyphosphate (polyP) level in stationary phase. The aim of the present work was to evaluate the influence of polyP levels as the involvement of low-affinity inorganic phosphate transport (Pit) system in E. coli copper tolerance.